The effect of financial performance on environmental disclosure of mining sector companies listed on IDX - Erwin Norma Arifiyanto (STIE Perbanas Surabaya, 2016)
This study aims to examine the effect of financial performance on environmental dis-closure in mining sector companies listed on the Indonesia Stock Exchange (IDX) 2012-2014. The data were analyzed using multiple linear regression analysis, with a significance level of 0.05. The samples used in this study are mining sector companies listed on the Indonesia Stock Exchange 2012-2014 and they disclosed their annual reports and environmental condition for three consecutive years. The results of this study show that the variable of profitability has an effect on environmental disclosure. However, when controlled using variable control, it has no effect. Meanwhile, the variable of Tobin's Q has no effect on environmental disclosure either controlled or not controlled by other variables. The implication of this study is that companies should improve their financial performance and environmental disclosure that could provide good news to public. So, the publication of financial statements and environmental disclosure can be useful not only for shareholders but also stakeholders.